Clinical Research in a Modern Chinese Peritoneal Dialysis Center. Issue 2 (June 2014) - Dong, Jie; Zhao, Ming-hui
A prerequisite for enhancing the quality of peritoneal dialysis is the continuous review and analysis of clinical data from routine clinical care and research. Here, we describe our strategy (Peking University First Hospital, Beijing, China) to achieve that objective.